2023
DOI: 10.1007/s10018-023-00377-x
|View full text |Cite
|
Sign up to set email alerts
|

Do renewable energy and total factor productivity eliminate CO2 emissions in Turkey?

Shahriyar Mukhtarov

Abstract: This paper analyzes the impact of renewable energy consumption, total factor productivity (TFP), income, imports, and exports on consumption-based CO2 emissions in Turkey from 1990 to 2019, utilizing the Autoregressive Distributed Lagged (ARDL) method. The findings indicated that the use of renewable energy, total factor productivity and exports negatively influence CO2 emissions. On the other hand, the positive impact of income and imports on CO2 emissions was found. The negative impact of renewable energy co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 93 publications
3
0
0
Order By: Relevance
“…Enhancing efficiency may result in a decrease in waste generation and energy consumption, leading to a reduction in carbon dioxide (CO2) emissions per unit of production. Additionally, our findings are in line with some studies like Mukhtarov (2023), Huang et al (2020), Mensah et al (2018), Alvarez-Herranz et al (2017, Li et al, (2017) concluded that technological progress (or TFP) reduces CO2 emissions.…”
Section: Empirical Results and Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Enhancing efficiency may result in a decrease in waste generation and energy consumption, leading to a reduction in carbon dioxide (CO2) emissions per unit of production. Additionally, our findings are in line with some studies like Mukhtarov (2023), Huang et al (2020), Mensah et al (2018), Alvarez-Herranz et al (2017, Li et al, (2017) concluded that technological progress (or TFP) reduces CO2 emissions.…”
Section: Empirical Results and Discussionsupporting
confidence: 93%
“…Thus, a rise in the utilization of renewable energy, generated from non-fossil fuel sources, would lead to a decline in CO2 emissions. Our results are consistent with the results of several studies in the case of different countries, such as Waheed et al (2018), Khoshnevis Yazdi & Shakouri (2017), Hasanov et al (2021), Raihan &Tuspekova (2022), andMukhtarov (2023), which revealed a negative effect of renewable energy consumption on CO2 emissions.…”
Section: Empirical Results and Discussionsupporting
confidence: 93%
See 1 more Smart Citation